2014
DOI: 10.1051/e3sconf/20140301015
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Green Building’s Criteria

Abstract: Abstract. Designers and clients alike are now emphasising on how to make their buildings green. Currently a lot of green councils worldwide are dealing with innovative ways to implement energy efficient new buildings. They have adopted various criteria and rating systems in an endeavour to classify buildings that contribute to environment sustainability, efficiency and users health. The aim of the paper is to present an overview of the criteria adopted by selected green building councils. This paper discusses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 2 publications
(1 reference statement)
0
14
0
1
Order By: Relevance
“…The green rating tools for Malaysia is managed by the Green Building Index (GBI) which was established in August 2008 by the Association of Architects Malaysia (PAM) that exclusively caters for buildings in a tropical climate (Bahaudin, Elias, & Saifudin, 2014 Bahaudin et al (2014), who did a comparative study between Malaysia's GBI and several other countries' assessment criteria, posit that the tools are only focusing on finished buildings thus it should also include assessments during the design and planning phases to ensure that minimum externalities occur during the following construction phase. The latter contributes the most negative effects on the environment (Bahaudin et al, 2014;Ikau, Joseph, & Tawie, 2016). Waste from design phase is caused by, among a few others, lack of experience in construction waste; long project duration; and lack of design information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The green rating tools for Malaysia is managed by the Green Building Index (GBI) which was established in August 2008 by the Association of Architects Malaysia (PAM) that exclusively caters for buildings in a tropical climate (Bahaudin, Elias, & Saifudin, 2014 Bahaudin et al (2014), who did a comparative study between Malaysia's GBI and several other countries' assessment criteria, posit that the tools are only focusing on finished buildings thus it should also include assessments during the design and planning phases to ensure that minimum externalities occur during the following construction phase. The latter contributes the most negative effects on the environment (Bahaudin et al, 2014;Ikau, Joseph, & Tawie, 2016). Waste from design phase is caused by, among a few others, lack of experience in construction waste; long project duration; and lack of design information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, even though numerous researches have highlighted the benefits of sustainable construction practice (Abidin, 2010;Sundayi et al, 2015;Whang & Kim, 2015;Afzan, 2016;Meron & Meir, 2017), construction practitioners seem to have little interest in adopting sustainable construction practice (Yahya & Abidin, 2013;Brennan & Cotgrave, 2014;Rostami et al, 2015;Afzan, 2016;Darko et al, 2017). Surveys have indicated this lack of support is due to the higher initial cost of sustainable building construction, which is termed "green cost premium" (Ahn et al, 2013;Bahaudin et al, 2013;Hwang & Ng, 2013;Brennan & Cotgrave, 2014;Shang & Peng, 2014;Qian et al, 2015;Sundayi et al, 2015;Afzan, 2016;Dodge Data & Analytics, 2016;Dwaikat & Ali, 2016;Mao et al, 2016;Amiril et al, 2017;. The following are several examples explaining the current problem regarding sustainable building construction and its higher initial cost:  A study conducted on various types of sustainable buildings, such as residential, educational, office, commercial, public buildings, and health facilities, showed that the additional cost to construct such buildings is up to 12.5% (WorldGBC, 2013) and 5% to 10% (Hwang et.al, 2017) of the total construction budget.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out in order to analyze and compare different methodological approaches of green rating systems [22][23][24][25]. More in detail, several studies focused on the analysis and comparison of specific macro-areas of green building rating systems, in order to evaluate the different weights assigned to the sub areas in each protocol.…”
Section: Introductionmentioning
confidence: 99%